2014
DOI: 10.3389/fnagi.2014.00311
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic Dysfunction and Inflammation in Alzheimer’s Disease: A Possible Connection

Abstract: Inflammation is observed in Alzheimer’s disease (AD) subject brains. Inflammation-relevant genes are increasingly implicated in AD genetic studies, and inflammatory cytokines to some extent even function as peripheral biomarkers. What underlies AD inflammation is unclear, but no “foreign” agent has been implicated. This suggests that internally produced damage-associated molecular pattern (DAMPs) molecules may drive inflammation in AD. A more complete characterization and understanding of AD-relevant DAMPs cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 158 publications
(207 reference statements)
1
32
0
Order By: Relevance
“…Numerous inflammatory pathways appear activated in AD brains, and interestingly elevated cytokines are observed both within AD subject brain tissue and patient sera [11, 16, 18, 21, 22]. Inflammatory signals classically initiate in response to a pathogen, or “foreign” agent.…”
Section: Neuroinflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous inflammatory pathways appear activated in AD brains, and interestingly elevated cytokines are observed both within AD subject brain tissue and patient sera [11, 16, 18, 21, 22]. Inflammatory signals classically initiate in response to a pathogen, or “foreign” agent.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…It is increasingly recognized that mitochondrial dysfunction and inflammation are interdependent lesions [11, 13]. Overall, though, the underlying cause(s) of these changes are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may be subjected to the Mini-Mental Status Examination (MMSE) if their clinician suspects abnormal cognitive performance. Pathologically, AD is a diverse and complex disease affecting nearly every subcellular system of the affected neurons (Oddo 2008;Tu et al 2014;Moh et al 2011;Wilkins et al 2014). One primary pathological characteristic has been identified as being an accumulation of amyloid-beta 1-40 and 1-42 (Aβ 1-40 and Aβ 1-42 ) though the primary amyloidogenic product implicated in AD has been Aβ 1-42 (Glabe 2001;Walsh and Selkoe 2004).…”
Section: Introductionmentioning
confidence: 99%
“…INPP5D , mainly expressed in hematopoietic cells, plays an important role in a series of inflammatory responses [8]. It has also reported that INPP5D was implicated in the pathogenesis of LOAD through the regulation of microglial cell function [8, 9]. Recently, INPP5D rs35349669 polymorphism was recognized to be strongly associated with the development of LOAD in 74,046 Caucasians [10].…”
Section: Introductionmentioning
confidence: 99%